Response of Soil Respiration to Grazing in an Alpine Meadow at Three Elevations in Tibet - Gang Fu; Xianzhou Zhang; Chengqun Yu; Peili Shi; Yuting Zhou; Yunlong Li; Pengwan Yang; Zhenxi Shen (The Scientific World Journal)
Alpine meadows are one major type of pastureland on the Tibetan Plateau. However, few studies have evaluated the response of soil respiration (Rs) to grazing along an elevation gradient in an alpine meadow on the Tibetan Plateau. Here three fenced enclosures were established in an alpine meadow at three elevations (i.e., 4313 m, 4513 m, and 4693 m) in July 2008. We measured Rs inside and outside the three fenced enclosures in July–September, 2010-2011. Topsoil (0–20 cm) samples were gathered in July, August, and September, 2011. There were no significant differences for Rs, dissolved organic C (DOC), and belowground root biomass (BGB) between the grazed and ungrazed soils. Soil respiration was positively correlated with soil organic C (SOC), microbial biomass (MBC), DOC, and BGB. In addition, both Rs and BGB increased with total N (TN), the ratio of SOC to TN, ammonium N (NH4+-N), and the ratio of NH4+-N to nitrate N. Our findings suggested that the negligible response of Rs to grazing could be directly attributed to that of respiration substrate and that soil N may indirectly affect Rs by its effect on BGB.